Counterweight module, preparation method thereof and weight training device
By coating the surface of the metal particles with a flexible energy-absorbing sheet layer, a microcapsule buffer layer and an elastic nanomesh layer to form a gradient interface, the problem of interface failure between the metal particles and the thermoplastic elastomer during high-temperature and low-temperature conversion and long-term use is solved, achieving higher bonding stability and durability.
Patent Information
- Application Number
- CN202511090406.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-10-10
AI Technical Summary
The interface structure between metal particles and thermoplastic elastomers in existing counterweight products is prone to stress mismatch during high-temperature and low-temperature transitions and long-term use, leading to interface delamination, cracks and structural failure. The existing chemical coupling agent method has poor stability and is difficult to act evenly.
A multi-layer flexible buffer structure is adopted, including a flexible energy-absorbing sheet layer, a microcapsule buffer layer and an elastic nano-membrane layer to coat the metal particles, forming a gradient interface. It is connected through physical coating and electrostatic adsorption to avoid chemical bonding and improve bonding stability.
It significantly improves the bonding stability between metal particles and the coating layer, reduces particle mobility and interface cracking caused by thermal expansion and contraction and mechanical vibration, and improves the durability and service life of the structure.
Smart Images

Figure CN120754505A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of composite materials, and more particularly to a counterweight module, a preparation method thereof and a weight training device. BACKGROUND
[0002] Wearable weight training devices are widely used in the fields of sports training, medical rehabilitation, physical fitness assessment, etc. They mainly provide necessary mass load by embedding metal counterweight particles such as iron sand and steel particles in the coating layer, while meeting the comfort and fit during wearing. For example, CN101007204A discloses a weight training device comprising a thermoplastic elastomer and a solid powder, wherein the solid powder is mixed with the thermoplastic elastomer, and the counterweight particles are fixed in the thermoplastic elastomer by injection molding or other processes.
[0003] However, due to the large difference in the thermal expansion coefficients between the metal particles and the thermoplastic elastomer, the interface structure is prone to stress mismatch during the temperature environment conversion process from the product manufacturing stage to the use stage, which may cause problems such as particle loosening, interface delamination, and even structure rupture.
[0004] More specifically, the counterweight product is usually in a high-temperature environment during the injection molding stage, such as the injection temperature of the polyurethane coating layer being 140-200℃. In this process, the molten polyurethane material coats the metal particles, and the solidification and setting are completed when the coating material shrinks upon cooling. However, the metal particles have large thermal capacity and small thermal expansion and contraction, so they cannot deform synchronously with the coating material during the cooling stage. Microscopic voids, residual stress zones, and even initial cracks are easily formed on the surface of the particles, and repeated deformation of this area during use may cause cracking, which poses a hidden danger for long-term use.
[0005] On the other hand, after the product is put into use, when the product is repeatedly exposed to alternating cold and hot scenarios, such as outdoor training→indoor air conditioning environment, the environmental temperature is usually -10-60℃, and the interface structure is prone to deterioration and failure due to stress concentration and long-term fatigue. Moreover, due to the influence of complex environmental factors such as long wearing time, repeated bending, and sweat intrusion, the interface material may also experience slow thermal fatigue and deformation accumulation.
[0006] In the prior art, chemical coupling agents such as silane coupling agents are often used to modify the surface of the metal particles to enhance the bonding force between the metal particles and the thermoplastic elastomer. However, the above method has the following limitations: on the one hand, the stability of the coupling agent system is limited and it is prone to degradation over time; on the other hand, high-energy treatment methods cannot uniformly act on the surface of the particles, and the environmental adaptability is poor.
[0007] Therefore, there is an urgent need for a multi-layer buffer interface structure that can withstand both the high-temperature-to-low-temperature rapid cooling during the manufacturing process and the mild repeated thermal expansion and contraction during long-term use, and realize stable combination between metal particles and flexible elastomers without relying on chemical bonding means. SUMMARY
[0008] To solve the problems of high risk of particle migration or peeling of existing counterweight products and interface failure caused by thermal expansion and contraction, the application provides a counterweight module, which realizes a gradient interface from a high-density core to flexible materials outside by introducing a multi-layer flexible and buffer material structure on the surface of metal particles, effectively disperses impact, absorbs load, and enhances the interfacial bonding force between the coating layer and the metal particles, significantly improving the stability and durability of the overall structure.
[0009] The application also provides a preparation method of the counterweight module.
[0010] The application also provides a weight training device with the counterweight module.
[0011] The technical scheme adopted by the application is to provide a counterweight module, which comprises counterweight particles and a coating layer, the coating layer wraps the counterweight particles, the counterweight particles comprise metal particles, and the surface of the metal particles is wrapped with a flexible energy-absorbing sheet layer, a microcapsule buffer layer and an elastic nanometer net film layer from inside to outside. The flexible energy-absorbing sheet layer is composed of liquid crystal polymer or graphene oxide material, and the thickness is 100-500 nm.
[0012] The counterweight module provided by the application has the following advantages and technical effects in structural design: 1. In the application, the counterweight particles adopt a composite structure with metal particles as the core, wrapped with a flexible energy-absorbing sheet layer, a microcapsule buffer layer and an elastic nanometer net film layer in sequence, the multi-layer flexible functional material is used to transition and connect the metal and the coating layer, a gradient flexible and rigid structure is formed, the combination stability of the particles and the overall injection coating layer is significantly improved, and the problems of particle separation, peeling or interface cracking caused by thermal expansion and contraction or mechanical vibration are reduced.
[0013] 2. In the application, the flexible energy-absorbing sheet layer is composed of liquid crystal polymer (LCP) or graphene oxide (GO), and the thickness is 100-500 nm. The layer has good mechanical compliance and sheet slip performance, can maintain structural integrity under high temperature and high pressure during injection molding, can absorb shrinkage stress during the coating layer forming and cooling process, can buffer the first heavy shear load from movement and impact during wearing and using, plays a role similar to a buffer support, and realizes flexible transition between the metal particles and the external elastic material.
[0014] 3. In the process of injection molding, the elastic nanometer net film layer can be physically embedded and penetrated with the coating material such as polyurethane, so as to improve the overall interface anchoring force; meanwhile, the nanometer net film has certain antibacterial performance and humidity permeability, which helps to improve the skin wear hygiene and stability.
[0015] 4. All the functional layer materials have thermal stability at >250℃ in the injection molding stage, so as to ensure that they will not be decomposed, delaminated or cross-linked out of control under high temperature and high pressure; and in the use temperature range of 30-40℃, the composite structure plays the functions of thermal response release, elastic stress regulation, phase change energy absorption and the like, so as to ensure the stability of particle positioning and the consistency of structure in the process of dynamic movement and weight training.
[0016] 5. In the present application, the four-layer structure forms a multi-scale configuration of "core-shell-buffer-permeation" at the particle level, which does not rely on any covalent grafting, plasma treatment or chemical coupling agent in the prior art, but only constructs the interface relationship through physical coating, electrostatic adsorption and net film embedding, which not only reduces the manufacturing complexity and environmental sensitivity, but also facilitates the large-scale injection molding production; meanwhile, it avoids the "interface hard collision" failure mode caused by the direct contact between traditional soft glue and metal, significantly improves the reliability of the structure under repeated bending and impact state, and finally improves the service life of the weight module.
[0017] According to one embodiment of the present application, the metal particles are selected from one or more combinations of iron, lead, tungsten, copper or molybdenum; and / or the density of the metal particles is 7.5g / cm³-19.0g / cm³. This structure significantly improves the unit volume weight density, so that the overall volume is smaller and more compact, facilitating wear, and meeting the requirements of high load and light weight.
[0018] According to one embodiment of the present application, the microcapsule buffer layer comprises a coating material and a core material, the coating material is polyurea, and the core material is n-decane or a mixture thereof with a melting point of 35-45℃. In the present application, the core material in the microcapsule buffer layer is selected as a phase change material of n-decane with a melting point of 35-45℃, which will not melt or decompose in advance at the injection molding temperature of 160-250℃, and the shell is stably coated with polyurea or a high-crosslinking polymer, which maintains the structural integrity in the cooling molding; when the wearing body temperature is in the range of 35-37℃, the phase change material releases latent heat, realizes micro-area temperature regulation and absorbs mechanical stress, delays the local accumulation of sweat and heat, and improves the wearing comfort.
[0019] According to one embodiment of the present application, the elastic nanometer net film layer is composed of cellulose nanocrystals and zinc oxide nanoparticles, and the thickness is 1-10μm. The elastic nanometer net film layer is composed of cellulose nanocrystals (CNC) and zinc oxide nanoparticles (ZnO), forms a micrometer-thick porous network with a thickness of 1-10μm, and has good interface roughness and polar coordination ability.
[0020] According to one embodiment of the present invention, the coating layer is composed of one or more materials selected from thermoplastic elastomer, silicone or rubber, has high flexibility and good molding properties, and can form a physical nesting structure with the nanomembrane layer to prevent particles from falling off.
[0021] According to one embodiment of the present invention, a heat-pressed composite fabric is attached to the outer surface of the covering layer and comprises a moisture-conducting layer, a buffer layer, and a connecting layer, the connecting layer being heat-pressed to the covering layer. Due to the high mass of the counterweight module, prolonged use can cause the fabric and counterweight to separate. Therefore, the connecting layer provides a secure and durable bond, significantly improving service life and structural integrity.
[0022] According to one embodiment of the present invention, the moisture-conducting layer is made of moisture-conducting polyester fiber; and / or the buffer layer is made of polyester elastic mesh; and / or the connecting layer is made of hot-melt TPU film. The moisture-conducting layer can be made of moisture-conducting polyester fiber to quickly drain away sweat; the buffer layer is made of polyester elastic mesh, providing a certain thickness of tactile cushioning and flexible support; and the connecting layer is made of hot-melt TPU film to enhance the hot-melt bond strength between the composite fabric and the weight module.
[0023] In order to realize the structure of the above-mentioned counterweight module, the present invention also provides a method for preparing the counterweight module, comprising the following steps: S1. Surface treatment is performed on the metal particles, and the metal particles are coated with a flexible energy-absorbing sheet layer, a microcapsule buffer layer, and an elastic nano-membrane layer in sequence to form a composite particle structure; S2, mixing the composite particle structure with the coating layer material and injecting it into the mold cavity, and performing overmolding at a temperature of 160° C. to 250° C.; S3, cooling and demoulding the formed structure to obtain the counterweight module.
[0024] According to an embodiment of the present invention, in step S2, a composite fabric is pre-placed on the inner wall of the mold cavity and fixed by vacuum adsorption.
[0025] The present invention also provides a weight training device comprising any of the aforementioned weight modules, which are incorporated into clothing, straps, or a backpack assembly to provide a weighted load. This training device offers the advantages of flexibility, safety, and adjustability, making it suitable for fitness, rehabilitation training, or specialized operations. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or prior art description. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without any creative effort based on these drawings.
[0027] Figure 1 A sectional view of the counterweight module in the embodiment of the present application.
[0028] Figure 2 A sectional view of the counterweight particle in the embodiment of the present application.
[0029] Explanation of reference numerals in the drawings: 1, counterweight particle; 2, coating layer; 3, composite cloth; 11, metal particle; 12, flexible energy-absorbing sheet layer; 13, microcapsule buffer layer; 14, nanometer net film layer; 31, connecting layer; 32, buffer layer; 33, moisture-conducting layer. DETAILED DESCRIPTION
[0030] The embodiments of the present application will be described in detail below, and examples of the embodiments are shown in the drawings, wherein the same or similar reference numerals represent the same or similar elements or elements having the same or similar functions throughout. The embodiments described below by referring to the drawings are exemplary and are only used to explain the present application, and cannot be understood as a limitation of the present application.
[0031] Combination Figures 1-2 As shown, in the present embodiment, a counterweight module is disclosed, which comprises a counterweight particle 1 and a coating layer 2, the coating layer 2 wraps the counterweight particle 1, the counterweight particle 1 comprises a metal particle 11, and the surface of the metal particle 11 is sequentially wrapped from inside to outside by a flexible energy-absorbing sheet layer 12, a microcapsule buffer layer 13 and an elastic nanometer net film layer 14. The flexible energy-absorbing sheet layer 12 is composed of liquid crystal polymer or graphene oxide material, and the thickness is 100-500 nm.
[0032] Specifically, the metal particle 11 can be selected from one or more combinations of iron, lead, tungsten, copper or molybdenum, and the density range is 7.5 g / cm 3 to 19.0 g / cm 3 , for providing a high-density counterweight effect. The metal particle 11 can be selected from one or more combinations of iron alloy, lead alloy, tungsten alloy, copper alloy or molybdenum alloy, and is not limited to pure metal. The density of the metal particle 11 varies with the type or grade of the alloy. The particle size of the metal particle 11 is generally controlled to be 200 μm to 500 μm, so as to obtain good fluidity and forming consistency.
[0033] Further, the flexible energy-absorbing sheet layer 12 is attached to the outer surface of the metal particles 11 by electrostatic adsorption or physical wrapping, with a thickness controlled within 100-500 nm, to provide the first rigid-flexible transition structure, and the sheet layer slip performance can absorb the shrinkage stress during injection molding and impact load during use, reducing internal stress concentration of the structure.
[0034] Further, the microcapsule buffer layer 13 is wrapped outside the flexible energy-absorbing sheet layer 12, composed of a phase change material core material of polyurea shell and n-decane or its mixture, with a core material melting point of 35-45℃ and a microcapsule particle size of 5-15μm. This structure is used to achieve slow-release energy absorption and temperature control in the body temperature zone, while maintaining thermal stability during injection molding.
[0035] Further, the elastic nanomesh membrane layer 14 is composed of cellulose nanocrystals and zinc oxide nanoparticles, forming a porous nanonetwork structure with a thickness of 1-10μm. This layer is used to enhance the interface anchoring between the coating layer 2 and the weight particles 1, and to achieve physical fixation through permeation and intercalation, while providing humidity regulation and antibacterial ability.
[0036] Further, the coating layer 2 can be selected from thermoplastic elastomers, silicone or rubber materials, preferably using injection molding process to coat the outside of the composite particles, with a molding temperature range of 160-250℃, to achieve effective packaging and mechanical stability of the composite structure. The thermoplastic elastomer material has good flexibility, resilience and molding processability, including but not limited to: thermoplastic polyvinyl chloride (PVC), thermoplastic polyolefin elastomer (TPO / TPV), thermoplastic polyurethane (TPU), styrene-based thermoplastic elastomer (SBS, SEBS, collectively referred to as TPS), thermoplastic polyester elastomer (TPEE), polyamide-based thermoplastic elastomer (PEBA, PAE), etc. The above materials can be reasonably selected according to the requirements of wear resistance, softness, aging resistance and adhesion performance with the composite fabric 3 in different use scenarios. Among them, TPU material has high tensile strength and excellent skin contact comfort, suitable for coating application of wearable weight products.
[0037] Further, the composite fabric 3 layer is attached to the outer surface of the coating layer 2, including a moisture-conducting layer 33, a buffer layer 32 and a connecting layer 31. The moisture-conducting layer 33 can use moisture-conducting polyester fibers to guide human sweat and enhance wear comfort; the buffer layer 32 uses polyester elastic mesh fabric to provide flexible cushioning and skin-friendly feel; the connecting layer 31 uses hot melt TPU film, which is hot-pressed and attached to the surface of the coating layer 2. Due to the large overall weight of the weight module, to avoid peeling of the composite fabric 3 layer during long-term use, the connecting layer 31 is set to improve the adhesion strength of the structure, ensuring stable attachment of the fabric layer to the coating layer 2 and enhancing the durability and service life of the structure.
[0038] The preparation method of the counterweight module in the present application comprises the following steps: S1, surface treatment is performed on the metal particles 11, and the flexible energy-absorbing sheet layer 12, the microcapsule buffer layer 13 and the elastic nanometer net film layer 14 are sequentially coated to form a composite particle structure; S2, the composite particles and the material of the coating layer 2 are mixed in a mass ratio of 1:1 to 5:1, injected into a mold cavity, and coated and formed at a temperature of 160°C to 250°C; S3, the formed structure is cooled and demolded to obtain a preliminarily formed counterweight module.
[0039] Further, in step S2, a composite cloth 3 layer is pre-arranged on the inner wall of the mold cavity, fixed on the inner surface of the mold cavity by vacuum adsorption, and the coating layer 2 and the connecting layer 31 are hot-melted and adhered through the injection molding process to realize synchronous integrated molding of the cloth and the module. Embodiment
[0040] The present embodiment provides a preparation method of a counterweight module, and the overall mass of the prepared counterweight module is 10 kg, which is used in a weight training equipment. The module adopts a multi-layer coating structure, the core of which is metal particles 11, which are sequentially coated with a flexible energy-absorbing sheet layer 12, a microcapsule buffer layer 13 and an elastic nanometer net film layer 14, and an outer side is provided with a thermoplastic polyurethane elastic coating layer 2, and the outermost layer is combined with a three-layer structure composite cloth 3 through a hot pressing process.
[0041] Firstly, high-purity spherical iron particles, Fe≥99.5%, brand: QLD-Fe100, particle size D90<100 μm are selected as the counterweight particles 1. 7.5 kg of iron particles are weighed and placed in a stainless steel cleaning tank with a stirring device, a neutral degreasing agent solution is added, and ultrasonic cleaning is performed for 10 minutes to remove surface oil stains. After cleaning, the particles are washed with deionized water, then soaked in a 5wt% nitric acid solution for 10 minutes to remove rust, and then washed with deionized water again, and dried to constant weight in a 60°C hot air drying oven for standby.
[0042] Then, in order to improve the impact buffering capacity of the counterweight particles 1 due to thermal expansion and contraction, a flexible energy-absorbing sheet layer 12 is deposited on the surface of the iron metal particles 11. Graphene oxide (GO) is used as the energy-absorbing material, and high-purity GO aqueous dispersion is used for coating, with a GO purity of >99% and a concentration of 0.5wt% supplied by ACS Materials. The GO solution is sprayed onto the surface of the dried iron particles at a ratio of 0.2 mL / g of iron metal particles 11 using a spraying device, and the metal particles 11 are kept rolling during the spraying process to ensure that each particle is evenly covered. After the spraying is completed, the particles are placed in a 60°C oven for 2 hours to dry, and the GO film forms a dense flexible energy-absorbing sheet layer 12.
[0043] The flexible energy-absorbing sheet layer 12 after coating the iron metal particles 11 is coated with a microcapsule buffer layer 13. The microcapsules used are prepared by in-situ interfacial polymerization, with high-purity n-decane as the core material (purity > 99.5%, Aladdin), and polyurea as the shell material, which is cross-linked from toluene diisocyanate (TDI, 98%, BASF) and ethylenediamine (EDA, 99%, Sigma-Aldrich). The emulsion preparation process is as follows: 50 g of n-decane is used as the oil phase, TDI is pre-dissolved in the oil phase, the water phase contains 2 wt% of Tween-80 emulsifier, the two phases are mixed at a volume ratio of 1:4, and emulsified under stirring at 1000 rpm to form a W / O emulsion with a droplet size of 10-30 μm. Then, under the condition of 25±2℃, the equivalent amount of EDA solution is slowly added for interfacial polymerization, and the reaction lasts for 2 hours. After the reaction is completed, the polyurea microcapsule powder with a particle size of about 20 μm is obtained by centrifugal separation at a speed of 5000 rpm for 10 minutes, three times of water washing, and drying at 60℃.
[0044] The dried microcapsule powder is mixed with the CNC / ZnO nanosuspension prepared in the next step at a mass ratio of 1:5 for co-deposition treatment. The materials used to prepare the elastic nanomesh membrane layer 14 slurry include cellulose nanocrystals (CNC, purity > 99%, BlueGoose Company, USA, concentration 2 wt%) and zinc oxide nanoparticles (ZnO particle size < 50 nm, purity 99.9%, Aladdin). 10 g of ZnO nanoparticles are added to 500 g of CNC water dispersion, mechanically stirred for 1 hour, and then ultrasonically treated for 30 minutes to prepare a uniform slurry. The above-mentioned composite slurry with microcapsules is uniformly sprayed on the surface of the iron particles deposited with GO layer by spraying process, and the spraying amount is 1.5 mL / cm². After completion, it is placed in a 60℃ environment for drying for 2 hours to form a porous elastic mesh membrane buffer layer 32. The total mass of the final counterweight particles 1 is about 8.0 kg.
[0045] Next, the elastic polyurethane coating layer 2 of the coated particles is prepared. The coating layer 2 raw material is Desmopan 2795A thermoplastic polyurethane from BASF company, with the addition of 1 wt% of chain extender 1,4-butanediol (purity 99%, Sigma-Aldrich) and 0.1 wt% of organic tin catalyst dibutyltin dilaurate (DBTDL, TCI company). After drying, the raw material is injected into the injection molding equipment, and the injection molding parameters are set as follows: barrel temperature 170℃, mold temperature 40℃, injection pressure 80 MPa, holding pressure time 15 seconds, and cooling time 30 seconds. Finally, an elastic coating layer 2 with an average thickness of 2 mm is formed. During the injection molding process, the composite particles and the polyurethane raw material are mixed uniformly at a mass ratio of 8:2 and then injected into the mold cavity to form a stable composite coating structure.
[0046] At the same time, the composite fabric 3 layer is prepared as the outermost layer of the fitting surface. The composite fabric 3 is composed of three layers of materials: the surface layer is a moisture-conducting layer 33 for contacting the human skin, which adopts Coolmax polyester moisture-conducting fiber with a grammage of 140 g / m², the middle layer is a buffer layer 32, which adopts 3D polyester elastic mesh fabric with a thickness of 2 mm, and the bottom layer is a connecting layer 31, which adopts hot melt TPU film with a thickness of 100 μm, and the manufacturer is Covestro. After the three kinds of fabrics are stacked in turn, the laminating equipment is used to press at a temperature of 150°C and a pressure of 0.3 MPa for 20 seconds, and after cooling and setting, the fabric piece matching the size of the inner wall of the mold cavity is cut, and the TPU film faces the inner side of the cavity for welding with the cladding layer 2.
[0047] Finally, the composite fabric 3 is prepositioned in the inner wall of the mold cavity for vacuum adsorption, the TPU film faces the inner cavity, and then the molten polyurethane-composite particle mixture is injected into the mold cavity, the mold is set to a temperature of 160°C, and the pressure is maintained for 15 seconds. After cooling, the mold is demolded, and a wearable weight module with a stable structure, a firmly attached surface composite fabric 3, and a total mass of 10 kg is obtained. Embodiment
[0048] The difference between the embodiment 1 is that the flexible energy-absorbing sheet layer 12 material in this embodiment uses liquid crystal polymer (LCP) instead of graphene oxide.
[0049] This embodiment provides a preparation method of a weight module, and the prepared weight module has a total mass of 10 kg. The structure still uses metal particles 11 as the core, which is sequentially coated with a flexible energy-absorbing sheet layer 12, a microcapsule buffer layer 13, and an elastic nanomesh membrane layer 14, and is provided with a thermoplastic polyurethane cladding layer 2, and the outermost layer is attached to a composite fabric 3 layer.
[0050] First, high-purity spherical iron particles are selected as the metal particles 11, Fe≥99.5%, QLD-Fe100, D 90 <100 μm as the weight core. 7.5 kg of iron metal particles 11 is weighed and placed in a cleaning tank, and neutral degreasing agent is added for ultrasonic cleaning for 10 minutes to remove surface oil stains. Then the particles are rinsed with deionized water, soaked in a 5wt% nitric acid aqueous solution for 10 minutes to remove rust, and dried to constant weight in a 60°C oven after rinsing again.
[0051] Then, the liquid crystal polymer flexible energy absorbing sheet layer 12 is prepared. In this example, commercially available LCP powder Vectra® A950 (Ticona, melting point about 280°C) is used as the main material, which is dissolved in a mixed solvent of toluene and NMP at a volume ratio of 3:1 by mass ratio of 5 wt% at 60°C for 2 hours to form a uniform transparent solution. Then, the LCP solution is uniformly sprayed on the surface of the dried iron particles using a spraying method, and the spraying amount is controlled to be 0.2 mL / g of particles. After spraying is completed, the particles are placed flat in a 60°C environment for 2 hours to dry, so that the solvent is completely volatilized, and the LCP forms a dense oriented flexible energy absorbing film layer on the surface of the particles.
[0052] The surface of the particles on which the LCP layer is deposited is further coated with a microcapsule buffer layer 13. This layer is prepared by in-situ interfacial polymerization of polyurea microcapsules, with high-purity n-decane as the core material (purity > 99.5%, Aladdin), and polyurea as the coating material, which is prepared by the reaction of TDI (98%, BASF) and ethylenediamine (99%, Sigma-Aldrich). The specific method is as follows: 50 g of n-decane and TDI form the oil phase, 2 wt% of Tween-80 emulsifier is dissolved in the water phase, emulsified at an oil-water ratio of 1:4, and stirred at 1000 rpm to form an emulsion with a particle size of 10-30 μm. Then, interfacial polymerization is carried out by slowly adding ethylenediamine solution at room temperature, and the reaction is carried out for 2 hours. After the reaction is completed, centrifugal separation is carried out at 5000 rpm for 10 minutes, and water washing is repeated three times, and drying is carried out at 60°C, to obtain microcapsule powder with an average particle size of 20 μm.
[0053] Next, the elastic nanomesh membrane composite slurry is prepared. First, 10 g of zinc oxide nanoparticles (ZnO, particle size < 50 nm, purity 99.9%, Aladdin) is slowly added to 500 g of 2 wt% CNC (cellulose nanocrystal, purity > 99%, Blue Goose Company) aqueous dispersion, and mixed under magnetic stirring for 1 hour, during which the stirring speed is maintained at 500 rpm, so that the ZnO is uniformly dispersed in the CNC liquid phase system. Then, dry treated polyurea microcapsule powder is added to the mixed solution at a slurry mass ratio of 1:5, and stirring is continued for 30 minutes for pre-mixing. Then, ultrasonic dispersion is carried out using an ultrasonic treatment device for 30 minutes, with a power of 200 W and an intermittent working mode, to obtain a CNC / ZnO / microcapsule composite slurry with uniform composition and stability. The slurry is uniformly sprayed on the surface of the metal particles 11 on which the LCP film has been deposited using a spraying device at a spraying amount of 1.5 mL / cm², and is placed in a hot air drying oven at 60°C for 2 hours to dry, to form a dense and porous elastic nanomesh membrane buffer layer 32. After drying is completed, the total mass of the counterweight particles 1 is about 8.0 kg.
[0054] Subsequently, the cladding layer 2 was prepared. Desmopan 2795A thermoplastic polyurethane (BASF) was selected as the raw material, with the addition of 1 wt% chain extender 1,4-butanediol (99%, Sigma-Aldrich) and 0.1 wt% organic tin catalyst DBTDL (TCI). After drying the raw material, it was put into an injection molding machine, with the barrel temperature set to 170°C, the mold temperature to 40°C, the injection pressure to 80 MPa, the holding pressure for 15 seconds, and the cooling time to 30 seconds. The above counterweight particles 1 were mixed with the TPU raw material in a mass ratio of 8:2 and then injected into the mold cavity to form a polyurethane elastic cladding layer 2 with an average thickness of 2 mm, ensuring the integrity of the overall structure.
[0055] At the same time, the composite fabric 3 layer was prepared. The fabric was composed of three layers: the surface layer was a moisture-conducting layer 33, using Coolmax polyester moisture-conducting fiber with a grammage of 140 g / m 2 The middle layer was a cushioning layer 32, using a 3D polyester elastic mesh with a thickness of 2 mm. The bottom layer was a connecting layer 31, using a hot melt TPU film with a thickness of 100 μm, and the TPU film manufacturer was Covestro. The layers were stacked in this order and then subjected to hot pressing treatment in a laminating machine, with the laminating temperature set to 150°C, the pressure to 0.3 MPa, and the pressing time to 20 seconds. After completion, the fabric was cooled and shaped, and then cut into a fabric piece matching the mold cavity, with the TPU film facing the inside of the mold cavity for standby use.
[0056] Finally, the composite fabric 3 was prepositioned in the inner wall of the injection molding mold, with the TPU film facing inward and tightly attached to the surface of the mold cavity. Then, the molten polyurethane material containing multiple layers of cladding particles was injected into the mold cavity, and the mold was closed and pressed, with the mold temperature set to 160°C. After holding pressure for 15 seconds, the mold was cooled and demolded, resulting in a complete counterweight module with a mass of 10 kg.
[0057] The final counterweight module has good energy-absorbing cushioning performance, structural stability, and skin-friendly comfort, making it suitable for use in training or rehabilitation equipment that requires wearable weight.
[0058] Comparative Example 1 The difference between this comparative example and Example 1 is that this comparative example uses metal particles 11 that have not been subjected to any functionalization treatment directly as the core structure.
[0059] First, high-purity spherical iron particles with Fe≥99.5%, model QLD-Fe100, and particle size D90<100 μm were selected as the counterweight particles 1. 8.0 kg of iron particles were weighed and placed in a stainless steel cleaning tank with a stirring device. Neutral degreasing agent solution was added, and ultrasonic cleaning was performed for 10 minutes to remove surface oil. After cleaning, the particles were rinsed with deionized water, then soaked in a 5 wt% nitric acid solution for 10 minutes to remove rust, and then rinsed thoroughly with deionized water. The particles were then dried in a 60°C hot air drying oven until constant weight, and were ready for use.
[0060] Subsequently, 8.0 kg of the dried iron particles were mixed with polyurethane thermoplastic elastomer at a mass ratio of 8:2, and an injection molding process was used to inject the cavity at a barrel temperature of 170°C and a mold temperature of 40°C to form a coating layer 2 with an average thickness of 2 mm.
[0061] After injection molding, a structural weight module was obtained, which did not have a flexible energy-absorbing sheet layer 12, a microcapsule buffer layer 13, and a nanometer net membrane layer 14 in its structure.
[0062] Comparative Example 2 The difference between this comparative example and Example 1 is that the surface of the iron particles in this comparative example was modified with a silane coupling agent to improve the interfacial bonding force with the polyurethane.
[0063] First, high-purity spherical iron particles with Fe≥99.5%, grade QLD-Fe100, and a particle size of D90<100 μm were selected as the weight particles 1. 8.0 kg of the iron particles were placed in a stainless steel cleaning tank with a stirring device, a neutral degreasing agent solution was added, and ultrasonic cleaning was performed for 10 minutes to remove surface oil stains. After cleaning, the particles were washed with deionized water, then soaked in a 5 wt% nitric acid solution for 10 minutes to remove rust, and then washed thoroughly with deionized water and dried in a 60°C hot air drying oven until a constant weight was obtained for later use.
[0064] Subsequently, the iron particles were soaked in a 1 wt% γ-aminopropyltriethoxysilane (KH-550) ethanol solution, stirred at room temperature for 1 hour, then dried, and then coated with an elastic polyurethane coating layer 2. The subsequent steps were the same as in Comparative Example 1.
[0065] Although the coupling agent treatment improved the adhesion between the metal particles 11 and the TPU interface to some extent, the flexible energy-absorbing sheet layer 12, the microcapsule buffer layer 13, and the nanometer net membrane layer 14 were not constructed, and the coating layer 2 still had problems of stress concentration and insufficient cushioning performance. After the durability bending test, local fatigue cracking occurred, and the wear fit was not good.
[0066] Comparative Example 3 Comparative Example 3 is basically the same as Example 1 or 2 in terms of the preparation process, except that the step of constructing the flexible energy-absorbing sheet layer 12 is omitted, i.e., the iron particles do not have a GO or LCP film layer deposited, and the subsequent deposition of the microcapsule buffer layer 13 and the elastic nanometer net membrane and the polyurethane coating are still performed.
[0067] Comparative Example 4 This comparative example omits the microcapsule buffer layer 13, and the remaining steps are the same as in Example 2. That is, an LCP energy-absorbing film layer and a CNC / ZnO elastic nanometer net membrane are sequentially deposited on the surface of the iron particles, and no polyurea microcapsule structure with n-decane as the core material is introduced.
[0068] Comparative Example 5 In this comparative example, the elastic nanomesh layer 14 is omitted, while the flexible energy absorbing sheet layer 12 and the microcapsule buffer layer 13 are retained. That is, the flexible energy absorbing sheet layer 12 and the microcapsule buffer layer 13 are sequentially deposited on the iron metal particles 11, but the CNC / ZnO mesh spraying is not performed, and the subsequent steps are the same.
[0069] Comparative Example 6 This comparative example demonstrates the critical importance of connecting layer 31 in composite fabric 3. In this comparative example, ordinary polyester fiber cloth replaces the hot-melt TPU film as the bottom connecting layer 31 of composite fabric 3. The remaining fabric structure is consistent with Example 1, still including the Coolmax moisture-conducting layer 33 and 3D elastic mesh.
[0070] Test example In order to verify the structural stability and service life of the counterweight module of the present invention under repeated bending and impact conditions, comparative tests were carried out on the counterweight modules prepared in Examples 1-2 and Comparative Examples 1-6. The test contents included repeated bending fatigue test, free drop impact test and hot and cold alternating fatigue test.
[0071] 1. Repeated bending fatigue test Each sample was subjected to repeated bending tests using an Instron 8874 dynamic multiaxial fatigue testing machine to simulate the accumulated stresses experienced while being worn. The weighted modules were fixed to a flexible fixture with a spacing of 200 mm. Reciprocating bending loads were applied at ±30° with a loading frequency of 2 Hz and a cycle count of 20,000. The test environment was maintained at a temperature of 25 ± 2°C and a relative humidity of 60%. After testing, the samples were observed for damage to their surface and internal structures. A comprehensive score was assigned out of 30 for structural integrity, surface cracks, cracking of the coating layer 2, and particle migration.
[0072] 2. Free drop impact test Samples were dropped from a height of 1.5 m onto a 5 mm thick steel plate, simulating accidental drops and collisions during actual use. Each sample was dropped from the front, side, and corner surfaces, 10 times in each direction, for a total of 30 drops. The test temperature was maintained at 25 ± 2°C. After the drop, the samples were observed for cracks in the coating layer 2, structural collapse, fabric lift, or particle leakage. A drop stability score (maximum 30 points) was assigned based on microscopic observations and internal scans.
[0073] 3. Hot and cold alternating fatigue test The test used a Weiss WK3-340 thermal cycling test chamber with a set temperature range of -10°C to +60°C, and a heating and cooling rate of at least 3°C / min. Each weight module sample was placed in the chamber and tested according to the following cyclic process: first, the sample was cooled to -10°C and held for 20 minutes; then the temperature was increased to +60°C for 10 minutes; then the temperature was maintained at +60°C for another 20 minutes; and finally, the sample was cooled back to -10°C for 10 minutes. This process constituted a complete thermal cycling cycle, each lasting 60 minutes. Each sample was subjected to 100 cycles, totaling approximately 100 hours, simulating the thermal stress fatigue process caused by frequent transitions from indoor air-conditioned environments to outdoor high and low temperatures in a real-world wearable environment.
[0074] After the cyclic test, the samples were removed and allowed to rest at room temperature for 24 hours. Their appearance, presence of cracks or bulging in the surface coating 2, and the integrity of the connection between the composite fabric 3 and the coating 2 were then observed and recorded. Peel strength testing and high-magnification microscopic observation were also used to analyze the interface layer for signs of structural damage, such as microcracks, delamination, or stress concentration. Each sample was scored for thermal fatigue performance on a 30-point scale, with interfacial cracking, bulging in the coating 2, and overall structural stability each accounting for one-third of the score.
[0075] 4. Test Results The following table lists the structural stability scores and damage performance of each sample in the two tests: Sample No. Bending Test Score Drop Test Score Cold-Heat Cycle Score Total Score Damage Description Example 1 29 28 27 84 Minor surface indentation, no interface peeling, structure remains intact Example 2 28 27 26 81 Local interface slight bulging, no particle movement observed Comparative Example 1 20 17 12 49 Coating layer cracks severely, particles loosen largely Comparative Example 2 21 18 14 53 Adhesion layer cracks, particles appear edge delamination Comparative Example 3 24 22 18 64 Microcapsule breaks severely, particles displace Comparative Example 4 23 21 17 61 Elastic structure collapses, interface micro-cracks expand after impact Comparative Example 5 22 20 15 57 Internal microcapsule deforms severely, interface stress concentration Comparative Example 6 18 19 13 50 Cloth layer buckles, structure peels off more severely after heat and cold alternation 5. Test Conclusion The test results show that Examples 1-2 obtained high scores in both the repeated bending test and the drop impact test, indicating that the multi-layer collaborative structure of "metal particles 11 + flexible energy-absorbing sheet layer 12 + microcapsule buffer layer 13 + elastic nano-mesh layer 14 + coating layer 2" proposed in the present invention significantly improves the overall structural stability and durable service life of the counterweight module under cyclic mechanical loads, impact loads and alternating hot and cold environments.
[0076] Specifically, combined with the comparative analysis of Comparative Examples 1-6, the functions and contributions of each structural layer are summarized as follows: 1. The counterweight module in Comparative Example 1 lacks any intermediate functional layers. The structure consists solely of ferrous metal particles 11 and a polyurethane coating 2, without any intermediate energy-absorbing or buffering structure. Test results show that during the high-temperature, high-pressure injection molding process, a hard interface forms between the particles and the coating 2, leading to residual stress concentration after cooling. During use, the coating is prone to bulging and cracking under bending and impact loads, resulting in significant particle migration and the lowest overall module structural reliability. This demonstrates that the intermediate buffer layer 32 is crucial for stress dissipation.
[0077] 2. The weight module in Comparative Example 2 is treated with a coupling agent but lacks the energy-absorbing / buffering layer 32. The interface bonding between the particles and the polyurethane is improved by silane coupling agent modification based on Comparative Example 1. Although the initial structural adhesion is slightly improved, the lack of a flexible energy-absorbing layer and an elastic buffer layer 32 still cannot absorb the interface stress waves during loading, and local fractures and failures still occur after impact, indicating that simply improving adhesion cannot replace the multi-layer buffer mechanism.
[0078] 3. The weight module in Comparative Example 3 lacks a flexible energy-absorbing sheet layer 12. This sample omits the flexible energy-absorbing sheet layer 12 (such as LCP / GO), and the particles are in direct contact with the microcapsules, causing stress to be directly transmitted to the microcapsule layer. At the molding temperature and body temperature (~35°C) during use, the microcapsules are easily softened or broken by heat, and particle-to-particle sliding and irregular accumulation occur during use. Compared with the examples, the stability between the structural layers decreases, confirming the key role of the flexible energy-absorbing sheet layer 12 in building the interface transition and stabilizing the distribution of microcapsules.
[0079] 4. The weight module in Comparative Example 4 lacks a microcapsule buffer layer 13. This sample omits the microcapsule layer and only provides structural support with the energy-absorbing sheet and nanomesh film. Although the overall structure maintains a certain integrity under initial loading, the lack of energy dissipation mechanism causes cumulative damage due to rigid contact between particles during repeated impact, ultimately leading to the collapse of the inner coating layer 2, indicating that the microcapsule layer cannot be replaced in absorbing instantaneous impact kinetic energy and relieving contact damage.
[0080] 5. The weight module in Comparative Example 5 lacks an elastic nanomesh film layer 14, causing the microcapsules to be exposed in the high-temperature molten polyurethane environment during injection molding, and the microcapsules are easily broken by heat and pressure, resulting in uneven particle structures and a significant decrease in buffering performance during subsequent drop tests. The nanomesh film layer serves as a nanofiber skeleton, not only providing structural constraints but also preventing the buffer material from being damaged in the processing and use temperature range, maintaining the deformation elasticity and mechanical consistency of the overall structure.
[0081] 6. The connecting layer 31 in the weight module in Comparative Example 1 uses a non-TPU film. This structure uses ordinary polyester fabric as the composite fabric 3 connecting layer 31, which lacks the ability to bond with the coating layer 2 through heat melting, resulting in warped edges and layers during injection molding. In the actual use temperature range (30-40°C) or high-humidity environment, the fabric and the coating layer 2 further loosen or even peel apart. In contrast, the TPU film used as the connecting layer 31 in the examples effectively bonds with the polyurethane coating layer 2 during the molding process, achieving high adhesion and moisture-resistant connection, ensuring the comfort and long-term durability of the module in the wearing state.
[0082] 7. Example 1 uses LCP as the flexible energy-absorbing sheet layer 12 material, which has high thermal stability, with a glass transition temperature of about 100-140°C, and can still maintain structural integrity at an injection molding temperature of 170°C; it can also maintain flexibility and mechanical stability in the body temperature range, suitable for the working environment of the counterweight module. Compared with Example 2 of the GO scheme, the LCP system has stronger adaptability to the thermal environment and slightly better stability. The GO scheme in Example 2 has higher interfacial adhesion and thermal conductivity, and better thermal stress dispersion capability during high-frequency movement.
[0083] 8. The test results show that the multi-layer coating structure used in Example 1 and Example 2 can effectively alleviate the accumulation of interfacial residual stress caused by alternating cold and heat, maintain the integrity of the overall structure, and the coating layer 2 has no obvious cracking or particle exposure phenomenon, and the structure still has good adhesion and elastic response. The samples in Comparative Example 1 and Comparative Example 2, which do not have a buffer structure or are only treated with a chemical coupling agent, show obvious coating bulging, interfacial peeling, and particle loosening after the test; Comparative Examples 3-5, which omit the flexible energy-absorbing sheet, the microcapsule buffer layer 13, or the elastic nanomesh membrane layer 14, all show varying degrees of fatigue failure and interfacial degradation; the sample in Comparative Example 6, which uses a common connecting layer 31, shows problems such as lifting of the composite fabric 3 and edge delamination. The above results further prove that the multi-level buffer interface structure constructed by the flexible energy-absorbing sheet, the microcapsule buffer layer 13, and the elastic nanomesh membrane layer 14 can significantly improve the structural durability and service life of the counterweight module in the alternating cold and heat stress field.
[0084] Although the embodiments of the present application have been shown and described above, it should be understood that the above embodiments are exemplary and should not be construed as limiting the present application, and those skilled in the art can make changes, modifications, replacements and variations to the above embodiments within the scope of the present application.
Claims
1. A counterweight module, characterized in that: The invention comprises a weight particle (1) and a coating layer (2), wherein the coating layer (2) wraps the weight particle (1), the weight particle (1) comprises a metal particle (11), and the surface of the metal particle (11) is sequentially coated with a flexible energy-absorbing sheet layer (12), a microcapsule buffer layer (13), and an elastic nano-membrane layer (14) from the inside out; Wherein, the flexible energy-absorbing sheet layer (12) is made of liquid crystal polymer or graphene oxide material and has a thickness of 100-500 nm.
2. A counterweight module according to claim 1, characterized in that: The metal particles (11) are selected from a combination of one or more of iron, lead, tungsten, copper or molybdenum; and / or The density of the metal particles (11) is 7.5 g / cm 3 -19.0g / cm 3 .
3. The counterweight module according to claim 1, characterized in that: The microcapsule buffer layer (13) comprises a coating material and a core material, wherein the coating material is polyurea, and the core material is n-decane or a mixture thereof having a melting point between 35°C and 45°C.
4. The counterweight module according to claim 1, characterized in that: The elastic nanomembrane layer (14) is composed of a composite of cellulose nanocrystals and zinc oxide nanoparticles, and has a thickness of 1 μm to 10 μm.
5. The counterweight module according to claim 1, characterized in that: The coating layer (2) is composed of one or more materials selected from the group consisting of thermoplastic elastomer, silicone rubber, and rubber.
6. The counterweight module according to claim 1, characterized in that: It also includes a heat-pressed composite fabric (3), which is adhered to the outer surface of the covering layer (2) and includes a moisture-conducting layer (33), a buffer layer (32), and a connecting layer (31), wherein the connecting layer (31) is used for heat-pressing connection with the covering layer (2).
7. A counterweight module according to claim 6, characterized in that: The moisture-conducting layer (33) is a moisture-conducting polyester fiber; and / or The buffer layer (32) is a polyester elastic mesh; and / or The connecting layer (31) is a hot-melt TPU film.
8. A method for preparing a counterweight module according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, performing surface treatment on the metal particles (11), and sequentially coating the metal particles with a flexible energy-absorbing sheet layer (12), a microcapsule buffer layer (13), and an elastic nano-membrane layer (14) to form a composite particle structure; S2, mixing the composite particle structure with the coating layer (2) material and injecting it into the mold cavity, and performing overmolding at a temperature of 160° C. to 250° C.; S3, cooling and demoulding the formed structure to obtain the counterweight module.
9. The method for preparing a counterweight module according to claim 8, characterized in that: In step S2, a composite fabric (3) is pre-placed on the inner wall of the mold cavity and fixed by vacuum adsorption.
10. A weight training device, characterized in that: The weight balancing module comprises the weight balancing module according to any one of claims 1 to 7, wherein the weight balancing module is arranged in clothing, a strap or a backpack component to provide a weight balancing load.
Citation Information
Patent Citations
Weight training device
CN101007204A